(untitled) (Third Sector Social Economic Review, 2023)
Companies compete on the basis of their supply chains today. This makes it necessary for the companies to manage their supply chains more effectively and efficiently. This construct made up of many partners that need to work in harmony also requires coordinated performance of a wide range of operations which regularly interact with each other. Transportation which accounts for the mobility in a supply chain and which basically provides place utility is one of the most important operations in a supply chain, with its impact on numerous critical matters including desired customer service level, competitive power, customer satisfaction and in particular, production and operating costs. In addition to its economic effects, transportation has all along played a significant role in the emergence of trade, trading routes and centers, thus, in the establishment and development of civilizations. Based on its aforementioned importance, this study investigated the development of transportation operations in Türkiye and provided a periodical performance analysis for a time period covering the years 2004-2021. Taking a wide range of criteria into consideration during analyses was the main reason for the preference of Multi-Criteria Decision Making (MCDM) methods which suggest appropriate solution algorithms for evaluating performance of a finite set of alternatives by using a finite set of criteria. Since there are numerous MCDM methods in the literature, those which are more up-to-date and which have not yet commonly been subject matter of applications were searched for. In this context, it was decided to use MEthod based on the Removal Effects of Criteria (MEREC), one of the objective weighting techniques, for weighting the evaluation criteria to be used for the analyses and Compromise Ranking of Alternatives from Distance to Ideal Solution (CRADIS) for determining the performance scores. In this study, in addition to the performance analysis, a sensitivity analysis was carried out in order to determine what kind of an effect the weighting of evaluation criteria would have on the findings obtained through the combined use of MEREC and CRADIS methods. To this end, the weights of the evaluation criteria were recalculated using Integrated Determination of Objective Criteria Weights (IDOCRIW) method, the resulting weights were used as input in CRADIS method and then the analyses were repeated.